2006
DOI: 10.1537/ase.050802
|View full text |Cite
|
Sign up to set email alerts
|

Ovalocytosis without band 3 gene 27-bp deletion and malaria infection

Abstract: Genetic adaptation to malaria is a longstanding research topic in anthropology and human genetics. Southeast Asian ovalocytosis (SAO) has been documented to have resistance to malaria; however, the implications of existing data are controversial. In particular, SAO resistance to malaria is unlcear in terms of the types of SAO, with/without the 27-base pair deletion in the band 3 gene (B3∆27). To shed light on the relationships between SAO and malaria, we surveyed Plasmodium infection, erythrocyte morphology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The higher frequency of SAO in the population of malaria endemic area of Southeast Asia and Melanesia supports the hypothesis that this genetic defect provides relative resistance to malaria. Subsequent studies reported that erythrocytes from SAO subjects are not resistant to invasion by P. falciparum but that the condition is associated with protection against severe malaria in children [ 16 , 17 ]. The mechanism(s) by which SAO confers protection to severe malaria remains unclear but some evidence indicates that it may be associated with reduced cytoadherence [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher frequency of SAO in the population of malaria endemic area of Southeast Asia and Melanesia supports the hypothesis that this genetic defect provides relative resistance to malaria. Subsequent studies reported that erythrocytes from SAO subjects are not resistant to invasion by P. falciparum but that the condition is associated with protection against severe malaria in children [ 16 , 17 ]. The mechanism(s) by which SAO confers protection to severe malaria remains unclear but some evidence indicates that it may be associated with reduced cytoadherence [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies reported that erythrocytes from SAO subjects are not resistant to invasion by P. falciparum but that the condition is associated with protection against severe malaria in children [ 16 , 17 ]. The mechanism(s) by which SAO confers protection to severe malaria remains unclear but some evidence indicates that it may be associated with reduced cytoadherence [ 13 , 17 ]. In this regard, it is of particular interest to explore further whether the frequency of SAO, at least among the ethnic population of Indonesia, is associated with malaria endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published between 1977 and 2015, with the majority (43.8%) published between 2000 and 2010 16 , 17 , 28 , 31 , 32 , 35 , 37 . Study designs included cross-sectional studies (50.0%) 16 , 17 , 28 , 30 , 31 , 34 , 36 , 37 , case–control studies (18.8%) 26 , 27 , 29 , cohort studies (25.0%) 32 , 33 , 35 , 38 and both cohort and case–control studies (6.3%) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 1977 and 2015, with the majority (43.8%) published between 2000 and 2010 16 , 17 , 28 , 31 , 32 , 35 , 37 . Study designs included cross-sectional studies (50.0%) 16 , 17 , 28 , 30 , 31 , 34 , 36 , 37 , case–control studies (18.8%) 26 , 27 , 29 , cohort studies (25.0%) 32 , 33 , 35 , 38 and both cohort and case–control studies (6.3%) 15 . Most studies were conducted in Papua New Guinea (68.8%) 15 , 16 , 26 , 28 , 29 , 32 36 , 38 , with the remainder in Indonesia (18.8%) 17 , 31 , 37 , Malaysia (6.3%) 30 and Thailand (6.3%) 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with SAO are characterized as having oval-shaped red blood cells with increased membrane rigidity and decreased anion transport, but no clinical symptoms beyond sporadic associations with anemia in both adults and neonates (Amato and Booth, 1977;Coetzer et al, 1996;Laosombat et al, 2005;Laosombat et al, 2010;O'Donnell et al, 1998;Reardon et al, 1993;Schofield et al, 1992). The deletion mutation that causes SAO removes 9 amino acids from within the 11 th exon of SLC4A1 and distinguishes SAO from other forms of ovalocytosis in Southeast Asia (Kimura et al, 2006;Patel et al, 2001).…”
Section: Sao Is Widespread In Island Southeast Asia and Neighboring Rmentioning
confidence: 99%